Flipped Classroom Learning among Medical and Dental Faculty of Bahria University Medical and Dental College - Dr. Shafaq Sultana; Prof. Dr. Talea Hoor; Dr. Madiha Ata (Pakistan Journal of Medicine and Dentistry, 2024)
Background: Flipped classroom technique (FCR) is a pedagogical approach where students watch pre-recorded video lectures or read educational materials before coming to class. During class time, students then engage in activities, discussions, and problem-solving exercises related to the pre-recorded content, with the teacher acting as a facilitator and guide. The key to the effective utilization of this instructional method is that both the teachers and the students understand its educational philosophy and technique. This study aims at exploring the faculty’s understanding and perceptions regarding flipping the classroom.